Short Communication: Estimation of aboveground biomass and carbon stock in agroforestry areas of Mergolangu and Karangsambung Villages, Wonosobo, Central Java, Indonesia (Asian Journal of Agriculture, 2024)
Abstract. Larasati AD, Abrari FH, Fathoni MFM, Jabbar SA, Arifiani KN, Indrawan M, Sugiyarto, Setyawan AD. 2024. Short Communication: Estimation of aboveground biomass and carbon stock in agroforestry areas of Mergolangu and Karangsambung Villages, Wonosobo, Central Java, Indonesia. Asian J Agric 8: 161-168. Carbon stock is an essential indicator in assessing ecosystem services that can reduce greenhouse gas emissions in the atmosphere, thereby helping to reduce the negative impacts of global climate change. Vegetation in agroforestry systems is vital in carbon storage and climate change mitigation. As a tropical country, Indonesia is vulnerable to the negative impacts of climate change. Wonosobo, the research location, is a district in Central Java Province, Indonesia. This study aims to estimate aboveground biomass and carbon stock of agroforestry areas in Mergolangu and Karangsambung Villages, Wonosobo, Central Java, Indonesia. The method used is simple random sampling at three research stations, i.e.: Mixed agroforestry (Station I), Agathis-based agroforestry (Station II), and Pine-based agroforestry (Station III). Of the three stations, the most extensive carbon stock was produced by Mixed agroforestry with an Aboveground Biomass (AGB) of 2,169.24 MgB/ha and carbon stock of 1,019.54 MgC/ha, followed by Agathis-based agroforestry with an AGB of 443.20 MgB/ha and carbon stock of 208.30 MgC/ha and Pine-based agroforestry with AGB amount of 359.10 MgB/ha and carbon stock of 158.14 MgC/ha.
Keywords: Allometric equation, biomass, carbon stock, forest, pole and tree